Design of non destructive testing on composite material using parallel plate electrical capacitance tomography: a conceptual framework - Abd Rashid, Wan Norhisyam; Mohamad, Elmy Johana; Abdul Rahim, Ruzairi; Subki, Shamsul Rahimi; Ahood, Abdul Latiff; Kadmin, Ahmad Fauzan; Naim @ Mohayat, Mohd Hariz; Ahmad, Mazran; Mohd Taha, Mohd Aliff (Penerbit Universiti Teknologi Malaysia Press, 2017)
In this paper, a conceptual framework for a non destructive testing to check defect on composite material using parallel plate electrical capacitance tomography is being proposed. At the early stage, the possibility of using this method is being simulated using Comsol Multiphysic software. The simulation process has shown promising results to make this concept works. When a dielectric material is placed between the parallel plates, the permittivity distribution can be observed. As the number of electrodes of the sensor are increased from 2 to 8 electrodes, the capacitance value increase from 2.0131e-11-2.3532e-14i F to 5.2474e-11-3.0756e-13i F. Furthermore, there are significant results when the size and the permittivity of the object are varies.